Comunicação intercultural em um programa de mobilidade acadêmica internacional. - Mello, Karla Ramos Ribas de (2024)
The present master's thesis examined how Intercultural Communication Competence contributed to International Academic Mobility among students of different nationalities. The study was conducted through exploratory qualitative research using participant observation procedures regarding the phenomenon of interculturality among Brazilian and international students of Complexity Engineering, from the partnership between the Catholic University of Pernambuco (Unicap) and the Institut Catholique d'Arts et Métiers (Icam) in France, during the International Academic Mobility Program. The adopted methodology involved qualitative data analysis techniques, including in-depth interviews, with the aim of understanding the importance of Intercultural Communication Competence within an International Academic Mobility Program. The specific objectives included understanding ICC, revealing its importance as a facilitator of students' integration and academic success during International Academic Mobility. Additionally, the results highlighted the influence of prior preparation, both linguistic and cultural, on adaptation and the utilization of international experience. The analysis also revealed a significant improvement in participants' linguistic skills throughout the program, demonstrating the positive impact of intercultural immersion. Based on the findings, the study aims to develop, as a final product, entitled "Interculturality Module," applicable to groups of Brazilian and international students who will undergo International Academic Mobility as part of their study program. The outcome of this work has the potential to impact other Icam campuses worldwide.